Figur Ayah dan Orientasi Masa Depan Remaja Sma Negeri Kota Bandung - Anggita Marshanda Farahdina; Khasanah, Andhita Nurul (Bandung Conference Series: Psychology Science, 2024)
Abstract. Future orientation is crucial, especially during high school when adolescents begin to think about and prepare for the future. The existence of a father figure as a role model and mentor will help adolescents about their future orientation. This study aims to determine the level of future orientation of adolescents seen from father figures who play a role in parenting. This research design uses descriptive quantitative method using cluster random sampling technique. The characteristics of the participants of this study are public senior high school students in the city of Bandung with an age range of 15 to 18 years. The participants obtained amounted to 528 respondents. The measuring instrument used is the theoretical model of Future Orientation built by Seginer, Nurmi, and Poole (1991) developed by Winurini (2021) for Indonesian adolescents. The data analysis method in this study uses descriptive statistical methods using percentages and tables. The results showed that the level of adolescents' future orientation was in the moderate category. And adolescents see biological fathers as father figures who are involved in parenting. Abstrak. Orientasi Masa Depan merupakan hal yang krusial, terutama pada masa SMA ketika remaja mulai memikirkan dan mempersiapkan masa depan. Keberadaan figur ayah sebagai role model dan mentor akan membantu remaja mengenai gambaran masa depannya. Penelitian ini bertujuan untuk mengetahui tingkat orientasi masa depan remaja dilihat dari figur ayah yang berperan dalam pengasuhan. Desain penelitian ini menggunakan metode kuantitatif deskriptif dengan menggunakan teknik cluster random sampling. Karakteristik partisipan penelitian ini merupakan siswa SMA Negeri di kota Bandung dengan rentang usia 15 hingga 18 tahun. Partisipan yang didapatkan berjumlah 528 responden. Alat ukur yang digunakan adalah model teoretikal Orientasi Masa Depan yang dibangun oleh Seginer, Nurmi, dan Poole (1991) yang dikembangkan oleh Winurini (2021) untuk remaja Indonesia. Metode analisis data dalam penelitian ini menggunakan metode statistik deskriptif dengan menggunakan persentase dan tabel. Hasil penelitian menunjukkan tigkat orientasi masa depan remaja berada pada kategori cukup. Serta remaja melihat ayah kandung sebagai figur ayah yang terlibat dalam pengasuhan.